Effects of Gasterophilus pecorum infestation on the intestinal microbiota of the rewilded Przewalski's horses in China. - Dini Hu (Public Library of Science (PLoS), 2021)
Horse botflies have been a threat to the Przewalski's horses in the Kalamaili Nature Reserve in Xinjiang of China since their reintroduction to the original range. As larvae of these parasites could infest the intestine of a horse for months, they could interact with and alter the structure and composition of its intestinal microbiota, affecting adversely its health. Nonetheless, there are no such studies on the rewilded Przewalski's horses yet. For the first time, this study characterizes the composition of the intestinal microbiota of 7 rewilded Przewalski's horses infected severely by Gasterophilus pecorum following and prior to their anthelmintic treatment. Bioinformatics analyses of the sequence data obtained by amplicon high throughput sequencing of bacterial 16S rRNA genes showed that G. pecorum infestation significantly increased the richness of the intestinal microbial community but not its diversity. Firmicutes and Bacteroidetes were found the dominant phyla as in other animals, and the parasitic infestation decreased the F/B ratio largely by over 50%. Large reduction in relative abundances of the two genera Streptococcus and Lactobacillus observed with G. pecorum infestation suggested possible changes in colic and digestion related conditions of the infected horses. Variations on the relative abundance of the genus groups known to be pathogenic or symbiotic showed that adverse impact of the G. pecorum infestation could be associated with reduction of the symbiotic genera Lactobacillus and Bifidobacterium that are probiotics and able to promote immunity against parasitic infection.